Caprine toxoplasmosis in Salta province, Argentina (FAVE Sección Ciencias Veterinarias, 2019)
Toxoplasmosis, caused by Toxoplasma gondii, is a zoonosis that causes reproductive losses in ruminants. This work characterised indirectly (by detecting antibodies) the disease presence in goats from Saltaprovince through a survey in 39 production units (PU). Biological samples were taken for a disease screening in which toxoplasmosis was included. The provincial average of positives PU was 79.49% and the average herd serum prevalence was 19.09% with values ranging between 2.8 y 78.13%, being more frequent values smaller than 20%. Positive PU were detected in all the provinces with the following averages of PU with positives animals: Saltean Chaco (SC)= 84.62%, Arid Ravines (AR)= 72.72%, Temperate Valleys (TV) = 80.00%. The ranges of seroprevalence were: CS= 3.50-20.00%, QA= 2.80-42.00% and VT= 6.25-78.13%. Antibodies against T. gondii were found in all the ecoregions of Salta province included in our study.
Keywords: Caprine; Toxoplasma; Argentina